The different stratospheric influence on cold-extremes in Eurasia and North America. Issue 1 (December 2018) - Kretschmer, Marlene; Cohen, Judah; Matthias, Vivien; Runge, Jakob; Coumou, Dim
Abstract The stratospheric polar vortex can influence the tropospheric circulation and thereby winter weather in the mid-latitudes. Weak vortex states, often associated with sudden stratospheric warmings (SSW), have been shown to increase the risk of cold-spells especially over Eurasia, but its role for North American winters is less clear. Using cluster analysis, we show that there are two dominant patterns of increased polar cap heights in the lower stratosphere. Both patterns represent a weak polar vortex but they are associated with different wave mechanisms and different regional tropospheric impacts. The first pattern is zonally symmetric and associated with absorbed upward-propagating wave activity, leading to a negative phase of the North Atlantic Oscillation (NAO) and cold-air outbreaks over northern Eurasia. This coupling mechanism is well-documented in the literature and is consistent with the downward migration of the northern annular mode (NAM). The second pattern is zonally asymmetric and linked to downward reflected planetary waves over Canada followed by a negative phase of the Western Pacific Oscillation (WPO) and cold-spells in Central Canada and the Great Lakes region. Causal effect network (CEN) analyses confirm the atmospheric pathways associated with this asymmetric pattern. Moreover, our findings suggest the reflective mechanism to be sensitive to the exact region of upward wave-activity fluxes and to be state-dependent on the strength of the vortex. Identifying the causal pathways that operate on weekly to monthly timescales can pave the way for improved sub-seasonal to seasonal forecasting of cold spells in the mid-latitudes. Atmospheric dynamics: Polar stratospheric influence on mid-latitude cold extremes Cold spells in the Northern Hemisphere mid-latitudes are influenced by the stratospheric polar vortex in two different ways. Marlene Kretschmer from the Potsdam Institute for Climate Impact Research, Germany, and collaborators use cluster analysis to show there are two dominant patterns associated with a weak polar vortex. The first is zonally-symmetric, associated with absorbed upward wave activity fluxes and is linked to a negative North Atlantic Oscillation and cold spells over Eurasia. Whilst the second is zonally-asymmetric, associated with downward reflected waves over Canada and is linked to a negative Western Pacific Oscillation and cold spells over North America. This knowledge could allow better prediction of winter weather on sub- to seasonal scales.